Review on State-of-the-Art Unidirectional Non-Isolated Power Factor Correction Converters for Short-/Long-Distance Electric Vehicles - Sawsan S. Sayed (16896414) (2022)
Electrification of the transportation sector has originated a worldwide demand towards green-based refueling infrastructure modernization. Global researches and efforts have been pondered to promote optimal Electric Vehicle (EV) charging stations. The EV power electronic systems can be classified into three main divisions: power charging station configuration (e.g., Level 1 (i.e., slow-speed charger), Level 2 (i.e., fast-speed charger), and Level 3 (i.e., ultra-fast speed charger)), the electric drive system, and the auxiliary EV loads. This paper emphasizes the recent development in Power Factor Correction (PFC) converters in the on-board charger system for short-distance EVs (e.g., e-bikes, e-trikes, e-rickshaw, and golf carts) and long-distance EVs (passenger e-cars, e-trucks, and e-buses). The EV battery voltage mainly ranges between 36 V and 900 V based on the EV application. The on-board battery charger consists of either a single-stage converter (a PFC converter that meets the demands of both the supply-side and the battery-side) or a two-stage converter (a PFC converter that meets the supply-side requirements and a DC-DC converter that meets the battery-side requirements). This paper focuses on the single-phase unidirectional non-isolated PFC converters for on-board battery chargers (i.e., Level 1 and Level 2 charging infrastructure). A comprehensive classification is provided for the PFC converters with two main categories: (1) the fundamental PFC topologies (i.e., Buck, Boost, Buck-Boost, SEPIC, Ćuk, and Zeta converters) and (2) the modified PFC topologies (i.e., improved power quality PFC converters derived from the fundamental topologies). This paper provides a review of up-to-date publications for PFC converters in short-/long-distance EV applications. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2022.3146410